654 Potential Longitudinal Association Between COVID-19 Infection Outcomes and Insomnia Symptoms. (3rd May 2021) - Vargas, Ivan; Muench, Alexandria; Grandner, Michael; Perlis, Michael
Abstract: Introduction: The COVID-19 pandemic has had an unequivocal negative impact worldwide, including increases in stress related to social isolation, unemployment, grief, and fear of contracting the virus. This increased stress has likely led to a greater prevalence of sleep continuity disturbance (i.e., insomnia) in the general population. The goal of the present study was to assess the prevalence of sleep continuity disturbance (i.e., insomnia) in the United States during the initial months of the pandemic. In addition, longitudinal assessment is currently ongoing in order to further assess participant experiences with COVID-19. Specifically, these follow-up data will be used to assess whether, among those that contracted COVID-19, insomnia at baseline (Time 1) predicts worse outcomes (e.g., symptoms of greater frequency, duration, or severity) upon follow-up (Time 2). Methods: A national survey was conducted from April-June 2020. Participants answered questions regarding social distancing practices, mood, sleep, physical activity, and COVID-19 symptoms. Insomnia symptom prevalence and severity were estimated with a retrospective sleep diary and the Insomnia Severity Index (ISI). A follow-up assessment is currently ongoing and will be completed in March 2021. The follow-up survey consists of similar questions and additional items regarding COVID-19 testing, symptoms [frequency, duration, and severity], and outcomes [outpatient treatment, incidence and duration of hospitalization, and incidence and type of respiratory assistance]. Results: 4, 133 adults (Mage = 45.8 years; range = 18 - 86 years; 78.7% female) completed the baseline survey. The prevalence of clinically significant sleep continuity disturbance (≥ 30 minutes) was 44.6% for sleep latency problems and 36.2% for wake after sleep onset problems. Nearly 34% of subjects reported average total sleep times of less than 7 hours. Over 17% of subjects (n = 719) reported total ISI scores in the clinical range (ISI total score ≥ 15). Conclusion: The present study suggests the prevalence of clinically significant insomnia symptoms during COVID-19 remain high in the general population (17–45% depending on definition of insomnia). Similarly, the prevalence of short sleep is elevated. Whether these incident data are associated with COVID-19 outcomes remains to be determined and will be the subject of follow-up analyses in January/February 2021. Support (if any): Vargas: K23HL141581; Perlis: K24AG055602